Sustainable Entrepreneurship Activities: A Pathway to Foster Intentions in Sustainability - Kartika Nuringsih; Edalmen Edalmen; Nuryasman MN (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objective: Aligning with the role of entrepreneurship education in higher education institutions (HEIs), the purpose of this study is to develop a model of sustainable entrepreneurship activities and analyze the relationship of these variables to sustainability education and sustainable entrepreneurial intentions. The application of sustainable entrepreneurial activities is to develop the thinking in Schlange's (2006) study in order to prepare knowledge for entrepreneurs in a sustainable era. Methodology: The respondents were entrepreneurship students in Jakarta, Indonesia. A total of 193 students were involved as respondents using purposive sampling technique while the data processing used Smart-Pls.Finding: The result proves the indicators are valid and reliable in reflecting these variables. It shows sustainable entrepreneurship activity and sustainable education affect the formation of sustainable entrepreneurial intention. Sustainable education mediates the formation of intention among students at the HEIs.Conclusion: The sustainable entrepreneurship activity as an instrument to be tested on respondents who have sufficient knowledge about SDGs. This result relates with the theory of planned behavior commonly used to examine the testing of entrepreneurial intentions. It is useful to determine the relevance of the triple bottom line theory. This study can transform the thoughts of Schlange as a pathway in understanding SDGs